PKP-012 Body surface area, cigarrete smoking and infliximab response in patients with psoriasi. (14th February 2016) - Colls, M; Padulles, N; Padullés, A; Notario, J; Bas, J; Sanmarti, N; Colom, H
Abstract : Background: Infliximab (IFX) is a chimeric anti-TNFα monoclonal antibody used in the treatment of psoriasis. Due to the large interindividual variability in IFX, measurement of serum concentrations and correlation with disease activity and different covariables could be useful for psoriasis management. Purpose: The primary endpoint was to assess the relation between IFX trough levels (Cmin ) and treatment efficacy. A secondary endpoint was to identify variables that could affect Cmin . Material and methods: Prospective study of patients with psoriasis treated with IFX between October 2013 and August 2015 at a tertiary level hospital. Cmin (mg/L) and antibodies against IFX (ATI) were determined at steady state by enzyme linked immunosorbent assay (ELISA) (Promonitor). Data recorded: sex, weight, BSA, PASI, dose regimen and cigarette smoking. Dose adjusted Cmin values were statistically compared after log transformation. Statistical analysis was performed using SPSS v.19. Results: 16 patients (25% women) were included. Median weight (kg) was 83.4 (Q1-Q3 65.5–93.8), median age (years) was 45 (Q1-Q3 38–54) years and median BSA (m 2 ) was 1.96 (1.66–1.96). 40 serum samples were available for analysis. Median IFX dose was 5 mg/kg/8 weeks (range 4 mg/kg/8 weeks to 5 mg/kg/6 weeks). All patients receiving dose intensified IFX had a BSA >1.7 m 2 . Median Cmin (mg/L) and dose adjusted Cmin (Cmin /D) (mg/L/mg/kg/month) were 1.59 (Q1-Q3 0.86–2.63) and 0.66 (Q1-Q3 0.37–1.1), respectively. 3 samples were positive for ATI. All patients who developed ATI had undetectable Cmin . Patients achieving PASI75 had a 23% higher Cmin /D compared with those not achieving PASI75. In patients with BSA >1.7 m 2, median Cmin and Cmin /D were 45% and 15% higher, respectively. Only 63% of patients with BSA >1.7 m 2 achieved PASI75 (compared with 100% of patients with BSA ≤1.7, p = 0.026); patients with BSA >1.7 m 2 and achieving PASI75 had a 36% higher Cmin /D compared with those not achieving PASI75. Median Cmin was 13.7% lower in cigarette smoking patients. Conclusion: Higher Cmin and Cmin /D values were associated with better treatment response in all patients. Patients with SC ≥1.7 showed a tendency to lower treatment response. Lower Cmin was found in smoking patients. More studies with a higher number of patients are needed to define the target levels and assess the influence of covariables. No conflict of interest.